Da Roma a gades : = De Roma a gades : gestione, smaltimento e riuso dei rifiuti artigianali e commerciali in ambiti portuali marittimi e fluviali = la gestión, eliminación y reutilización de residuos artesanales y comerciales en ámbitos portuarios marítimos y fluviales : Atti del Workshop Internazionale (Roma, 19-20 settembre 2019) : in omaggio/en homenaje a Simon Keay - Bernal Casasola, Darío; Contino, Alessia; Sebastiani, Renato (2022)
This volume, dedicated to the illustrious archaeologist Simon Keay, collects the scientific results of an international workshop held in Rome (2019), which discussed the management, elimination and reuse of artisanal and commercial waste in maritime and river ports, focussing on the Roman cities of Rome and Gades (modern day Cádiz).